Adsorption isotherms, kinetics, thermodynamics and desorption studies of 2,4,6-trichlorophenol on oil palm empty fruit bunch-based activated carbon - Ivy Tan, Ai Wei; Abdul Latif, Ahmad; Hameed, Bassim Hamid (Elsevier Ltd, 2009)
The adsorption characteristics of 2,4,6-trichlorophenol (TCP) on activated carbon prepared from oil palm empty fruit bunch (EFB) were evaluated. The effects of TCP initial concentration, agitation time, solution pH and temperature on TCP adsorption were investigated. TCP adsorption uptake was found to increase with increase in initial concentration, agitation time and solution temperature whereas adsorption of TCP was more favourable at acidic pH. The adsorption equilibrium data were best represented by the Freundlich and Redlich–Peterson isotherms. The adsorption kinetics was found to follow the pseudo-second-order kinetic model. The mechanism of the adsorption process was determined from the intraparticle diffusion model. Boyd plot revealed that the adsorption of TCP on the activated carbon was mainly governed by particle diffusion. Thermodynamic parameters such as standard enthalpy (ΔH°), standard entropy (ΔS°), standard free energy (ΔG°) and activation energy were determined. The regeneration efficiency of the spent activated carbon was high, with TCP desorption of 99.6%.